Fuzzy-PID Controller of robotic grinding force servo system - Adnan Jabbar Attiya; Yang Wenyu; Salam Waley Shneen (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
When a robot is used to grind or finish a curved surface ,as marine propeller surface, both contact force and feed movement must controlled at the similar time in order that the grinding tool would machine the work-piece, with  required  force, at  the  right  position  in  right  posture. A compliant wrist system  is advanced, in  this  paper, to conform the shape of the machining propeller by altering its posture along with the surface. Grinding force is controlled under a simple new Fuzzy-PID controller with five input variables which assembled and compared with an antecedently used PID controller. The aim of defining the rules and its optimization are to achieve a controller that provides grinding with higher quality. Both the controllers PID and Fuzzy-PID have been optimized together with the parameters of the Two-Phase Hybrid Stepping Motor The Fuzzy-PID controller  policy at a steady value in the normal direction of the mentioned machining point by multi-point machining, while the grinding tool moving along the curved surface of the propeller. It means that the model of the compliant wrist system and the surroundings could be used in force controlling when robots grind marine propeller surface by a grinding tool with multi-point machining. DOI: http://dx.doi.org/10.11591/telkomnika.v15i1.8051